1995
DOI: 10.1002/cbm.1995.5.2.85
|View full text |Cite
|
Sign up to set email alerts
|

Personality disorder in an outpatient offender population

Abstract: Previous research with incarcerated and hospitalised offenders has produced a fourfold typology of personality types. These have been labelled primary psychopath, secondary psychopath, inhibited and controlled. The current study uses cluster analysis of the Millon Clinical Multiaxial Inventory (MCMI) scores to determine whether the same clusters emerge in a sample of non‐incarcerated offenders. Results indicate the presence of the four types in this population. Consideration is given to how the clusters vary w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…However, the first psychopathic cluster was relatively free of additional pathology, whereas the second cluster exhibited high scores on scales measuring schizoid, avoidant, dependent and passiveaggressive traits. Wales (1995) suggested that the first group corresponded with previous accounts of primary psychopathy, and the second with accounts of secondary psychopathy. Blackburn and Coid (1999) employed the Structured Clinical Interview for DSM-III Axis II disorders (SCID-II) to establish six groups of criminal offenders based on psychiatric symptoms.…”
mentioning
confidence: 74%
“…However, the first psychopathic cluster was relatively free of additional pathology, whereas the second cluster exhibited high scores on scales measuring schizoid, avoidant, dependent and passiveaggressive traits. Wales (1995) suggested that the first group corresponded with previous accounts of primary psychopathy, and the second with accounts of secondary psychopathy. Blackburn and Coid (1999) employed the Structured Clinical Interview for DSM-III Axis II disorders (SCID-II) to establish six groups of criminal offenders based on psychiatric symptoms.…”
mentioning
confidence: 74%
“…Although the MCMI has been employed within offender populations (Carpenter, Peed, & Eastman, 1995;Hart, Forth, & Hare, 1991;Kelln et al, 1998; McCormack, Barnett, & Wallbrown, 1989;McNiel & Hever, 1990;Wales, 1995;Weekes, Morison, Millson, & Fettig, 1995;Wierzbicki & Howard, 1992), only two studies have examined its factor structure. McCormack, Barnett, and Wallbrown (1989) found 4 factors based on the combined clinical and personality scales of the MCMI-I.…”
mentioning
confidence: 99%
“…Finally, the fourth cluster, named controlled psychopath, was identified by a compulsive and dependent personality. These Blackburn typologies have been replicated using different samples in both nonimprisoned delinquents [6] and inmates held in a high security penitentiary institution [7] . A number of authors have used the MCMI-II with violent inmates, and diverse research programs [8,9] have demonstrated the utility of such a classification of the prison population, especially if employed in conjunction with the Minnesota Multiphasic Personality Inventory-2 (MMPI-2).…”
Section: Introductionmentioning
confidence: 99%